The Motivation of Young Argentinians of Lithuanian Origin to Learn the Lithuanian Language - Kalnaitytė, Lina; Vilkienė, Loreta (Taikomoji kalbotyra, 2024)
This paper describes a study that aims to answer the questions: what factors might encourage young Argentinians of Lithuanian origin to learn the Lithuanian language? What are the linguistic attitudes and opinions about Lithuania of young Argentinians of Lithuanian origin? What is their ethnic identity? The research analyzed the responses of 33 Argentinians of Lithuanian origin living in Lithuania and Argentina to a sociolinguistic form, a motivation questionnaire, and 5 semi-structured qualitative interviews with young Argentinians of Lithuanian origin living in Lithuania and Argentina. Descriptive statistics, qualitative analysis, and thematic analysis methods. The results of the data analysis show that the motivation of the research group to learn Lithuanian is quite strong. The research participants are most strongly motivated to learn Lithuanian by their positive attitudes towards the Lithuanian language, Lithuanians, and Lithuania and the weakest by the motivation of the ought-to L2 self. The regression analysis carried out in the study revealed that the motivation of the ought-to L2 self is stronger in the respondents living in Lithuania than in the participants of the research, who are living in Argentina. The older respondents and respondents who have lived in Lithuania for a longer time attitudes towards the Lithuanian language, Lithuanians, and Lithuania are less positive than among the younger respondents and respondents who have lived in Lithuania for a shorter time. Respondents who declared a stronger identity of Lithuanian have a stronger motivation to learn Lithuanian.
Keywords: foreign language learning motivation; language attitudes; ethnic identity; Argentinians of Lithuanian origin; sociolinguistic factors